Star Wars : Mace Windu. The twilight run - Bernardin, Marc (Marvel Worldwide, 2024)
One of the greatest Jedi Knights of all stars in his own comic book! Even in the years before the Clone Wars, Mace Windu was known for his discipline, determination and combat skills. They’ll all be put to the test as he vies to stop an incendiary secret from falling into the wrong hands! When a scientist’s discovery threatens the balance of the galaxy, Mace is led down a treacherous path of mystery and action! After working together to escape the menace of the Bore Worm, Mace and smuggler Azita Cruuz are pursued by a Hutt-hired bounty hunter on the refinery moon Ro Mira. But what else lies in their path? Who is following them? And what is Coaxium Ultra?